2011
DOI: 10.1182/blood-2010-12-324954
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of progenitors to the thymus limits T-lineage reconstitution after bone marrow transplantation

Abstract: T-cell production depends on the recruitment of hematopoietic progenitors into the thymus. T cells are among the last of the hematopoietic lineages to recover after bone marrow transplantation (BMT), but the reasons for this delay are not well understood. Under normal physiologic conditions, thymic settling is selective and either CCR7 or CCR9 is required for progenitor access into the thymus. The mechanisms of early thymic reconstitution after BMT, however, are unknown. Here we report that thymic settling is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 53 publications
(77 reference statements)
2
72
2
Order By: Relevance
“…Other findings also strongly support continued translational studies for the development of IT -based HSC transplantation strategies including: (a) a significantly more rapid kinetics of T-cell reconstitution following IT as compared to IV administration of HSC and (b) long-term thymopoiesis by IT-injected precursors in nonconditioned recipients, even across histocompatibility barriers (Fig. 2) [23,41,57,[60][61][62]. It will therefore be important to determine the clinical settings in which an IT transplantation approach, potentially enhancing HSC differentiation to a T lineage fate, will improve short-as well as long-term patient outcome.…”
Section: Future Perspectivesmentioning
confidence: 82%
“…Other findings also strongly support continued translational studies for the development of IT -based HSC transplantation strategies including: (a) a significantly more rapid kinetics of T-cell reconstitution following IT as compared to IV administration of HSC and (b) long-term thymopoiesis by IT-injected precursors in nonconditioned recipients, even across histocompatibility barriers (Fig. 2) [23,41,57,[60][61][62]. It will therefore be important to determine the clinical settings in which an IT transplantation approach, potentially enhancing HSC differentiation to a T lineage fate, will improve short-as well as long-term patient outcome.…”
Section: Future Perspectivesmentioning
confidence: 82%
“…Indeed, it has recently been shown that thymus permeability is increased by more than fivefold after myeloablative conditioning. 30 In our experiments, BM engraftment of conditioned mice treated by intravenous transplantation reached levels of more than 90%, but BM donor cells in intrathymic-transplanted mice were also elevated, accounting for at least 30% of lineage-negative BM progenitors ( Figure 5). The high BM engraftment of progenitors was associated with the maturation of donor B lymphocytes, although ZAP-70-deficient host precursors are completely capable of B-cell differentiation (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is striking that immediately after conditioning by irradiation, the requirement for CCR7/CCR9 is abolished. 30 Thus, it is possible that in our conditioned ZAP-70-deficient mice, the absence of donor progenitor cell expansion and/or long-term persistence after intrathymic transplantation is because of an early competition from incoming endogenous progenitors as well as the presence of a less favorable thymic niche.…”
Section: Discussionmentioning
confidence: 99%
“…Because the recipient thymus is impaired by the conditioning regimen (especially irradiation), the thymic reconstitution takes ∼10 wk; T cells are the last hematopoietic lineage cells to recover after BMT in mice and humans (32). To improve this situation, we combined TT with BMT to provide a new environment for T cell induction and differentiation.…”
Section: Discussionmentioning
confidence: 99%